QUALITY OF PUBLIC SERVICES THROUGH SOCIAL MEDIA - Didik Supriyanto, (International Journal of Social Science, 2023)
The Regional Government of Malang City responds to the impact of globalization with the urgency of digitizing communication media between the government and its people. The response aims to establish a two-way relationship between government and society. The purpose of this study was to determine the quality of public services through social media on the Twitter account @PemkotMalang. This study uses a qualitative descriptive approach by analyzing qualitative data through a 3-month observation period on several documents, the appearance of the Twitter account application and the results of the research which are explained through descriptions in the narrative. The results of this study found that there were several efforts made by the Malang city government to improve the quality of public services through the @PemkotMalang twitter account through easy access to the @PemkotMalang twitter account, increasing content on the @PemkotMalang twitter account, and updating data & information displays. Improving the quality of public services provided can improve the image of the Malang City government in the eyes of its people. The digitalization of communication media is demonstrated by the City of Malang demonstrating its existence as a region that upholds the principles of transparency in good governance through the use of a Twitter account.